2011
DOI: 10.3855/jidc.1704
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic Chlamydia pneumoniae infection and inflammatory markers in coronary artery disease patients

Abstract: Introduction: We evaluated the role of inflammation and acute or persistent Chlamydia pneumoniae infection in coronary artery disease (CAD).      Methodology: The study involved 63 cardiovascular disease patients diagnosed with angina and myocardial infarction (MI) and 40 healthy controls. ELISA was performed for detection of C. pneumoniae IgA antibodies and for quantitative analysis of IFN-γ. PCR was performed for detection of the C. pneumoniae 16 SrRNA gene in blood. Results: C. pneumoniae IgA antibodies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…Acute or persistent Chlamydia pneumoniae infection, as detected with polymerase chain reaction, was shown to correlate to CAD risk [15]. Acute or persistent Chlamydia pneumoniae infection, as detected with polymerase chain reaction, was shown to correlate to CAD risk [15].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Acute or persistent Chlamydia pneumoniae infection, as detected with polymerase chain reaction, was shown to correlate to CAD risk [15]. Acute or persistent Chlamydia pneumoniae infection, as detected with polymerase chain reaction, was shown to correlate to CAD risk [15].…”
Section: Introductionmentioning
confidence: 96%
“…Infections activate host immune responses, and there is evidence that they promote the process of atherosclerosis. Acute or persistent Chlamydia pneumoniae infection, as detected with polymerase chain reaction, was shown to correlate to CAD risk [15]. Studies propose a central role of interferon-gamma, suggesting an increased role of inflammation and inflammatory markers, not only in the initiation but also in the progression of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent reports (both serological studies and studies of outbreaks in confined populations [43,44]) show that it is still a widespread and successful respiratory pathogen. In addition to respiratory infections, C. pneumoniae has been linked with several other chronic conditions, most notably cardiovascular inflammatory diseases such as atherosclerosis, abdominal aortic aneurisms, and valvular lesions (45)(46)(47)(48). While there is a body of published evidence linking C. pneumoniae and cardiovascular disease, a causal link remains to be definitively proven and is considered controversial by some.…”
mentioning
confidence: 99%
“…Coronary artery atherosclerosis is considered as the main cause of cardiac disease. 3 Atherosclerosis is a common pathological process associated with acute and chronic coronary heart disease and ischemic stroke. Inflammation seems to be a key event in the development and progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 It is reported that India have the highest risk of CAD and the prevalence of CAD in India has recently been estimated to be 11%. 3 Serological studies indicate a prevalence rate of C. pneumoniae 40-70% in many countries. 9 Hence present study was conducted to determine the seroprevalence of C. pneumoniae antibody and association of chronic infection with CAD.…”
mentioning
confidence: 99%